COMPARATIVE ANALYSIS OF DERIVATIONAL PROCESSES IN ENGLISH AND UZBEK VOCABULARY SYSTEMS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
This article presents a comprehensive comparative analysis of derivational processes in the English and Uzbek vocabulary systems. Derivation, a fundamental linguistic mechanism, plays a pivotal role in the expansion and enrichment of lexicons in languages across the globe. By examining these processes in two linguistically distinct languages, we seek to uncover patterns, similarities, and differences that shed light on the intricate ways languages create and adapt words. Through a systematic investigation, this study offers insights into how English and Uzbek utilize derivational processes to generate new vocabulary, reflecting each language's linguistic diversity and inherent structure. The analysis explores the historical, cultural, and structural factors that influence derivational systems in these languages, ultimately contributing to our understanding of language evolution and the dynamic nature of vocabulary development.